Long-term combined application of organic and inorganic fertilizers increases crop yield sustainability by improving soil fertility in maize–wheat cropping systems - Jinfeng Wang; Xueyun Yang; Shaomin Huang; Lei Wu; Zejiang Cai; Minggang Xu (Journal of Integrative Agriculture, 2025)
Organic material combined with inorganic fertilizer has been shown to greatly improve crop yield and maintain soil fertility globally. However, it remains unclear if crop yield and soil fertility can be sustained in the long term under the combined application of organic and inorganic fertilizers. Three long-term field trials were conducted to investigate the effects of organic amendments on the grain sustainable yield index (SYI), soil fertility index (SFI) and nutrient balance in maize–wheat cropping systems of central and southern China during 1991–2019. Five treatments were included in the trials: 1) no fertilization (control); 2) balanced mineral fertilization (NPK); 3) NPK plus manure (NPKM); 4) high dose of NPK plus manure (1.5NPKM); and 5) NPK plus crop straw (NPKS). Over time, the grain yields of wheat and maize showed an increasing trend in all four fertilization treatments at the Yangling (YL) and Zhengzhou (ZZ) locations, while they declined at Qiyang (QY). The grain yield in the NPKM and 1.5NPKM treatments gradually exceeded that of the NPK and NPKS treatments at the QY site. The largest SYI was recorded in the NPKM treatment across the three sites, suggesting that inorganic fertilizer combined with manure can effectively improve crop yield sustainability. Higher SYI values were recorded at the YL and ZZ sites than at the QY site, possibly because the soil was more acid at QY. The key factors affecting grain yield were soil available phosphorus (AP) and available potassium (AK) at the YL and ZZ sites, and pH and AP at the QY site. All fertilization treatments resulted in soil N and P surpluses at the three sites, but soil K surpluses were recorded only at the QY site. The SFI was greater in the 1.5NPKM, NPKM and NPKS treatments than in the NPK treatment by 13.3–40.0 and 16.4–63.6% at the YL and ZZ sites, respectively, and was significantly higher in the NPKM and 1.5NPKM treatments than in the NPK and NPKS treatments at the QY site. A significant, positive linear relationship was found between SFI and crop yield, and SYI and nutrient balance, indicating that grain yield and its sustainability significantly increased with increasing soil fertility. The apparent N, P and K balances positively affected SFI. This study suggests that the appropriate amount of manure mixed with mineral NPK fertilizer is beneficial to the development of sustainable agriculture, which effectively increases the crop yield and yield sustainability by improving soil fertility.